1995
DOI: 10.1097/00006842-199503000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Quality of Well-Being Scale for Persons With Human Immunodeficiency Virus Infection

Abstract: To evaluate the validity of the Quality of Well-Being Scale (QWB) for studies of patients with human immunodeficiency virus (HIV) disease, 514 men were studied who were divided among four categories: Centers for Disease Control and Prevention (CDC) Group A (N = 272), CDC-B (N = 81), CDC-C (N = 47), and uninfected male controls (N = 114). The QWB and a variety of medical, neuropsychological, and biochemical measures were administered to all participants. When QWB scores were broken down by HIV group, the CDC-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…The QWB-SA was developed in 1996 as a selfadministered, scanable version of the Quality of Wellbeing Index (QWB), a previously validated measure of preference-based general health status [7,8] that has been used in populations with a variety of diseases [1,9,[11][12][13][14][15][16][17][18]. The QWB-SA assesses symptoms (acute and chronic) and functioning (self-care, mobility, physical activity, and social activity) to provide a health-utility score as a summary measure of QoL [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…The QWB-SA was developed in 1996 as a selfadministered, scanable version of the Quality of Wellbeing Index (QWB), a previously validated measure of preference-based general health status [7,8] that has been used in populations with a variety of diseases [1,9,[11][12][13][14][15][16][17][18]. The QWB-SA assesses symptoms (acute and chronic) and functioning (self-care, mobility, physical activity, and social activity) to provide a health-utility score as a summary measure of QoL [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Some examples are multiple versions of Medical Outcome Study (MOS). [6][7][8][9][10][11][12][13][14][15] We have used The World Health Organization Quality of Life (WHOQOL)-BREF [16,17] for measuring quality of life in 68 HIV patients in the same setup. [18] It provides scores on a scale of 0 to 100, which is often useful for assessing the outcome of a therapy in patients on followup.…”
mentioning
confidence: 99%
“…21 Further, the method has been used for health resource allocation modeling and has served as the basis for an innovative experiment on rationing of health care by the state of Oregon. 22,23 Studies have also demonstrated that the QWB is responsive to clinical change derived from surgery 14 or medical conditions such as rheumatoid arthritis, 24 AIDS, 10 and cystic fibrosis. 11 Th e QWB was developed more recently.…”
Section: Qol Measurement: Self-administered Quality Of Well-being Scalementioning
confidence: 99%